Psychobiological Effects of Choral Singing on Affective State, Social Connectedness, and Stress: Influences of Singing Activity and Time Course - Bullack, Antje; Gass, Carolin; Nater, Urs M.; Kreutz, Gunter (Frontiers in Behavioral Neuroscience, 2018)
Previous studies have suggested that there are complex psychobiological effects of amateur choral singing on wellbeing. Here, we investigate the influences of singing versus non-singing on psychological and biological measurements, reflecting current positive and negative affect, perceived social connectedness and physiological stress. We hypothesized that active singing leads to significant increases in these measurements compared to participating without singing. Amateur choristers (Exp. 1: N = 54, age range 18 to 85 years and Exp. 2: N = 49, age range 18 to 85 years) were tested in two experiments in which approximately half of the group was asked not to sing over periods of 30 (Exp. 1) and 60 minutes (Exp. 2), while the other half of the group sang. Dependent measures included scales for positive and negative affect and perceived social connectedness. In addition, saliva samples were collected to assess cortisol and alpha-amylase. The results revealed that singing activity had positive influences on affect measurements. However, significant increases in perceived social connectedness for singing were found only in Exp. 2. Biomarker changes were not significant across the experiments. Together, our findings suggest that both singing activity and duration of singing modulate psychological effects, with perceived social connectedness evolving over larger time spans than 30 minutes. Findings support the notion of beneficial psychological effects also for individuals, who report lower levels of general social support. The unexpected absence of biological effects warrants further investigation.